Imaging findings of hereditary renal tumors, a review of what the radiologist should know. Issue 101 (April 2018) - Czarniecki, Marcin; Gautam, Rabindra; Choyke, Peter L.; Turkbey, Baris
Highlights: It is estimated that 5–8% of renal cancers are non-sporadic and have a hereditary component. Known findings are described, as well as current follow-up and management recommendations. Extra-renal findings are summarized to aid the radiologist in identifying hereditary renal syndromes. Abstract: It is estimated that up to 8% of currently diagnosed renal cancers are part of a hereditary syndrome. The radiologist may be the first person to associate a renal tumor presenting during an imaging study to other manifestations of a hereditary syndrome. This diagnosis can have broad implications for the patient but also for other family members. This update reviews the current known associations and emerging mutations of hereditary renal cancers from a radiologist's perspective. Renal manifestations, as well as associated radiological findings and pitfalls are discussed. Additionally, screening and surveillance recommendations are also discussed to aid radiologists in the decision-making process for patient management.